UK Defence Supply Chain Relationships: a Study of Sustained Monopoly. - Humphries, Andrew; Wilding, Richard D. (Emerald Group Publishing Limited, 2004)
Business-to-business, supply chain relationships within sustained monopolies, such as those within UK Defence Procurement, have received scant attention by Management Researchers. This paper describes the results from a substantial, exploratory research project that used Williamson’s (1975) Organisations Failure Framework as a theoretical model. Surprisingly, it revealed that many issues surrounding Supply Chain Management implementation were similar to those found in ‘normal’ markets and that it played an important part in reducing the inherently negative effects of monopolistic relationships. The research sheds new and useful light on the dynamics of this unusual business situation for both managers and academics.
Keywords: Defence contractors; Defence sector; Monopolies; Public sector organizations; Supply chain management; United Kingdom